Portuguese in Germany: considering issues of heritage language development and biliteracy - Flores, Cristina (2021)
[Excerpt] Introduction: Germany has a strong tradition of immigration, which became an important feature of the German society from the early fifties on, when the country had to be rebuilt after its almost complete destruction during World War II. In the fifties and sixties, Germany signed bilateral recruitment agreements with several countries like Italy (1960), Turkey (1961) and Portugal (1964), allowing unqualified guest workers in the industrial sector to take positions with minimal training requirements (Feld et. al., 2017).[...]